Relational remembering : rethinking the memory wars - Campbell, Sue, 1956- (Feminist constructions., 2003)
"The harmful stereotypes of women's passivity and instability that have repopulated discussions of abuse have led many theorists to regard the social dimensions of remembering only negatively, as a threat or contaminant to memory integrity. Tracing the impact of the memory wars on science and culture, Relational Remembering offers a vigorous philosophical challenge to the contemporary skepticism about memory that is their legacy. Campbell uses the false memory debates to defend a feminist reconceptualization of personal memory as relational, social, and subject to politics."--Jacket